IMPLEMENTASI ALGORITMA RIJNDAEL DALAM KEAMANAN DATA FORMAT MULTIMEDIA - Wijaya, Andy; Hakim, Lukman (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
Multimedia data such as images, video, and audio are data formats that are often used in this world to easily provide information to another individual because they can be accessed with many device anywhere. Therefore, it is necessary to secure data security so that data security can be maintained properly and directed to the right person or group. It